Elodea Canadensis Michx. (Hydrocharitaceae)- A New Angiospermic Record for Bangladesh - Alfasane, Md Almujaddade; Hoque, Farhana Pervin; Hassan , Md Abul; Khan, Md Sabbir Mostafa (Bangladesh Journal of Plant Taxonomy, 2023)
A new angiospermic record, Elodea canadensisMichx. iselaborated with illustration. The detailed taxonomic description of the species with other relevant information are provided here. The present species has been collected from Hakalukihaor of Moulvibazar district of greater Sylhet. Bangladesh J. Plant Taxon. 30(2): 195-200, 2023 (December)